The Influence and Contribution of Macroeconomics to The Indonesian Sharia Stock Index for The Period 2011-2021 - Mulyadi, Sandi; Wibowo, Muhammad Ghafur (Universitas Muhammadiyah Surakarta, 2023)
This study aims to determine the impact of macroeconomic variables on the Indonesian Sharia Stock Index (ISSI). The macroeconomic variables used are Industrial Production Index (IPI), Indonesian Sharia Bank Certificate (ISBC), Money Supply (MS), Exchange Rates (ER), Interest Rates (IR), and inflation. The observed data is in the form of monthly data for the period 2011 to 2021. The method used is to test the impact and contribution of VECM. The test results with the VECM model found that in the short term, all variables had no effect on the Indonesian Sharia Stock Index, whereas, in the long term, IPI, ISBC, and inflation had a negative effect, and MS, ER, and IR had a positive effect, based on the IRF test showed that ISSI responding to fluctuations from all positive macroeconomic variables except inflation which responded negatively and the contribution of each macroeconomic variable was IPI (0.64), ISBC (2.01), MS (0.45), ER (0.64), IR (0.01), and inflation (1.16) against the Indonesian Sharia Stock Index.